Pengaruh Konseling Teknik Menyusui terhadap Kejadian Lecet Puting Susu pada Ibu Multipara - Henniwati, Henniwati; Fazdria, Fazdria; Harahap, Meliani Sukmadewi; Nurdahliana, Nurdahliana; Alchalidi, Alchalidi (Universitas Malahayati, 2024)
ABSTRACT A common problem in breastfeeding is nipple blisters/pain. Due to an error in the breastfeeding technique, the baby does not breastfeed until the areola is present. The impact that occurs if the breastfeeding technique is not correct is that it can cause breast swelling, mastitis/breast abscess, anatomical abnormalities in the nipples such as sinking nipples or flat nipples, nipple blisters and breast milk does not come out optimally. This study aimed to determine the effect of breastfeeding technique counseling on the incidence of nipple blisters. This type of research is quasi-experimental with a posttest control group design. The sample in this study was multiparous postpartum mothers totaling 36 people who were divided into two groups (control and treatment)—data analysis using the Mann-Whitney test. The study results obtained in the control group showed that the mean of 13.31 was lower than that of the treatment group, which was 23.69 and the Sig. 2-tailed obtained 0.001, it can be concluded that the provision of breastfeeding technique counseling affects the incidence of nipple blisters in postpartum women. The conclusion in this study is that providing counseling on breastfeeding techniques has an effect on the incidence of sore nipples in postpartum mothers. It is expected that health workers can always provide counseling on correct breastfeeding techniques to mothers. Keywords: Counseling, Breastfeeding Technique, Nipple Chafing ABSTRAK Masalah yang sering terjadi dalam proses menyusui adalah puting susu lecet/nyeri. Hal ini disebabkan kesalahan dalam teknik menyusui yaitu bayi tidak menyusui sampai ke areola. Dampak yang terjadi jika teknik menyusui yang tidak benar yaitu dapat menyebabkan payudara bengkak, mastitis/abses payudara, kelainan anatomis pada puting susu seperti puting susu yang tenggelam atau puting susu yang datar, puting susu lecet dan ASI tidak keluar optimal. Tujuan penenlitian untuk mengetahui pengaruh konseling teknik menyusui terhadap kejadian putting lecet. Jenis penelitian ini quasi eksperimen dengan desain posttest control group desain. Sampel pada penelitian ini ibu nifas multipara yang berjumlah 36 orang yang dibagi menjadi 2 kelompok (control dan perlakuan).Analisa data menggunakan uji mann-whitney test. Hasil penelitian didapat pada kelompok control rerata 13,31 lebih rendah dari pada rerata kelompok perlakuan yaitu 23,69 dan niali Sig. 2-tailed didapat 0,001, maka berate bahwa pemberian konseling tehnik menyusui berpengaruh terjadap kejadian putting lecet pada ibu nifas. Kesimpulan dalam penelitian ini pemberian konseling tehnik menyusui berpengaruh terjadap kejadian putting lecet pada ibu nifas. Diharapkan untuk tenaga kesehatan dapat selalu memberikan konseling tehnik menyusui yang benar kepada ibu. Kata Kunci: Konseling, Teknik Menyusui, Puting Lecet